Pengabdian Masyarakat melalui Edukasi Pencegahan Perundungan di SDN Pamoyanan Desa Padamaju (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Bullying remains a serious problem in primary education because it affects children’s psychosocial development, academic performance, and mental health. This community service program focused on educational efforts to prevent bullying at SDN Pamoyanan, Padamaju Village, Pagelaran Sub-district, Cianjur Regency. The aim of this activity was to increase students’ understanding of the definition, forms, impacts, and prevention strategies of bullying, as well as to foster collective awareness in creating a safe and inclusive learning environment. The method applied was a participatory research approach that involved teachers and students in every stage, from planning, implementation, to evaluation. Activities were carried out through observation, discussion, material presentation, simulation, and reflection. The results showed a significant increase in students’ knowledge, where before the intervention most of them did not understand the concept of bullying, but after the program, the majority were able to identify its forms and prevention steps. In addition, the program successfully built positive interactions and encouraged students to be more courageous in sharing their experiences and perspectives regarding bullying. Overall, the findings indicate that participatory-based education is effective in strengthening students’ understanding while fostering more empathetic and collaborative social attitudes. This activity is expected to continue sustainably by involving teachers, parents, and the wider community to strengthen bullying prevention efforts in primary schools.